2013
DOI: 10.1016/j.compscitech.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-grain discretization and full Mori Tanaka formulation for random heterogeneous media: Predictive abilities for stresses in individual inclusions and the matrix

Abstract: For modelling damage in short fibre composites, both the predictions of the effective properties and the stresses in the individual inclusions and in the matrix are necessary. Mean field theorems are usually used to calculate the effective properties of composite materials, most common among them is Mori-Tanaka formulation. Owing to occasional mathematical and physical admissibility problems with the Mori-Tanaka formulation; a pseudo-grain discretized Mori-Tanaka formulation (PGMT) was proposed in literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 26 publications
0
22
2
2
Order By: Relevance
“…Each fiber is represented by an ellipsoidal inclusion with its own aspect ratio, orientation and volume. We have demonstrated that this algorithm correctly calculates the homogenized elastic properties of the composite and that the stresses in fibers [31] and on the fiber-matrix interface [32] are calculated with an acceptable accuracy. We also have proven that for typical random fiber composites the degree of asymmetry of the stiffness tensor predicted with Mori-Tanaka method is limited and simple symmetrisation of the stiffness tensor provides an acceptable correction [33].…”
Section: Micromechanical Modellingmentioning
confidence: 99%
“…Each fiber is represented by an ellipsoidal inclusion with its own aspect ratio, orientation and volume. We have demonstrated that this algorithm correctly calculates the homogenized elastic properties of the composite and that the stresses in fibers [31] and on the fiber-matrix interface [32] are calculated with an acceptable accuracy. We also have proven that for typical random fiber composites the degree of asymmetry of the stiffness tensor predicted with Mori-Tanaka method is limited and simple symmetrisation of the stiffness tensor provides an acceptable correction [33].…”
Section: Micromechanical Modellingmentioning
confidence: 99%
“…The Mori-Tanaka (MT) formulation [3] is probably the most commonly used mean field homogenization scheme. It is known to predict with reasonable accuracy not only the effective response of the composite but also the stresses in individual inclusions [4] in spite of formal mathematical inconsistencies appearing in some specific cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of the Mori-Tanaka formulation [16] and an algorithm for treating fiber matrix debonding [17], this method predicts the local SN curve with only one SN curve as input. The approach was named the Master SN curve approach, in short the MSNC approach.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%